Visual Investigation of the Radial Energy Distribution of the Ions Produced by a Low Pressure Saddle Field Ion Source - Mahmood, Aras S. (Sulaimani Journal for Pure and Applied Sciences, 2002)
A simple Practical method is used to investigate the distribution of the positive ion in the beam produced by a low pressure saddle field ion source according to their energies. It was found that the more energetic ions are those in the central portion of the ion beam wile the ion energy decreases radially toward the edges of the beam.
Keywords: Saddle field ion source Energy distribution of the ions Vacuum system Thin film